Remote monitoring of implantable cardioverters defibrillators: a comparison of acceptance between octogenarians and younger patients - Šafaříková, Iva; null, null; Bulava, Alan; Hájek, Přemysl (Science Press, 2020)
Remote monitoring (RM) is increasingly employed for all types of cardiac implantable devices (CIED). However, there are only limited data on the acceptance of RM by the elderly. The aim of our study was to ascertain how octogenarians assess RM technolo- gies compared to younger, presumably technically more literate patients, and what concerns or technical problems the system presents to both groups of patients. Methods The trial was designed as a descriptive, register-based single-center study. The study population con- sisted of all consecutive patients ≥ 80 years of age (group A, n = 94) and all consecutive patients aged ≤ 40 years (group B, n = 71), who had undergone implantation of an implantable cardioverter-defibrillator (ICD) between the years of 2009 and 2018 and were using a Home MonitoringTM (HM, Biotronik, Berlin, Germany) system. All patients fulfilling entry criteria were approached with a request to participate in the survey. Results A total of 85 (90.4%) and 65 (91.5%) valid surveys were obtained for groups A and B, respectively. Ninety-two per- cent of patients in both groups (P = 0.903) were satisfied with the limited number of planned ambulatory follow-ups (i.e., once a year). All patients in both groups (100%) reported that they were satisfied with the HM system, and 97% and 94% of patients in Groups A and B, re- spectively, ranked it highly beneficial (P = 0.68). A significant proportion of patients in both groups were completely unaware of any health-related benefits associated with the use of the HM system (42% in Group A vs. 49% in Group B, P = 0.4). Among the most frequently reported personal benefits of HM were a sense of safety and security and savings on travel expenses and time. 5% and 9% of patients in Groups A and B, respectively, reported that usage of HM caused them some degree of psychological stress (P = 0.27). Nearly all patients in both groups reported receiving information on HM from their doctor after ICD implantation. None of Group A reported receiving informa- tion from a nurse either before or after ICD implantation, while 14% of Group B patients reported receiving information from a nurse after, but not before ICD implantation. Seven and 51% (P < 0.0001) of patients in Group A and B, respectively, sought additional information about HM post-discharge. Conclusions The HM system received good marks and was much appreciated, even in patients over 80 years of age. The level of acceptance and potential psychological stress resulting from RM technology appears to be about the same in older patients as in younger patients. The majority of octogenarians either did not fully understand the clinical benefits of the system or mistakenly thought that the HM system was a substitute for emergency 24-h surveillance. These results highlight the need for better patient education relative to RM technology, with one option being to delegate more of this educational process to specially trained nurses.
Keywords: Education; Implantable electronic devices; Remote monitoring; The elderly